1966
DOI: 10.1017/s2040618500035334
|View full text |Cite
|
Sign up to set email alerts
|

Certain fundamental congruences on a regular semigroup

Abstract: In recent developments in the algebraic theory of semigroups attention has been focussing increasingly on the study of congruences, in particular on lattice-theoretic properties of the lattice of congruences. In most cases it has been found advantageous to impose some restriction on the type of semigroup considered, such as regularity, commutativity, or the property of being an inverse semigroup, and one of the principal tools has been the consideration of special congruences. For example, the minimum group co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
43
0

Year Published

1971
1971
1991
1991

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(49 citation statements)
references
References 18 publications
5
43
0
Order By: Relevance
“…Some of our results overlap with those proved by Yamada in [12] in a somewhat different guise; on the other hand, there is some overlapping with the results of Howie and Lallement [5], proved there by different methods. We make frequent use of several results established in the last mentioned paper, and add to the list of interesting connections among special congruences on a regular semigroup.…”
supporting
confidence: 77%
See 1 more Smart Citation
“…Some of our results overlap with those proved by Yamada in [12] in a somewhat different guise; on the other hand, there is some overlapping with the results of Howie and Lallement [5], proved there by different methods. We make frequent use of several results established in the last mentioned paper, and add to the list of interesting connections among special congruences on a regular semigroup.…”
supporting
confidence: 77%
“…The proofs in [5] are different from ours. Several characterizations of the semigroups in Theorem 4.1 in terms of spined products were established by Yamada [12].…”
Section: \Jt:a-*(a*a5) (Aes)mentioning
confidence: 65%
“…The Green relations will be noted as usual, and for brevity, a semilattice of groups-congruence will be called a SG-congruence. That each of the above minimum congruences exists is explained in [5], and also noted there are some of the following relationships which will be useful here:…”
Section: Preliminary Results"mentioning
confidence: 99%
“…It was shown in [5] that ηΠσis the smallest congruence p such that S/p is a semilattice of groups and is unitary. Thus, in general, ξ is strictly contained in η Π σ.…”
mentioning
confidence: 99%
“…Proof. Howie and Lallement [2] have shown that J>* is the least semilattice congruence on 5. Hence (i) and (ii) are equivalent.…”
Section: Preliminariesmentioning
confidence: 99%